Ultrafast Modulation of Vibrational Polaritons for Controlling the Quantum Field Statistics at Mid-Infrared Frequencies - Herrera-Urbina, F; Triana-Galvis, J (IOP Publishing Ltd, 2022)
Controlling the quantum field statistics of confined light is a long-standing goal in integrated photonics. We show that by coupling molecular vibrations with a confined mid-infrared cavity vacuum, the photocount and quadrature field statistics of the cavity field can be reversibly manipulated over sub-picosecond timescales. The mechanism involves changing the cavity resonance frequency through a modulation of the dielectric response of the cavity materials using femtosecond UV pulses. For a single anharmonic molecular vibration in an infrared cavity under ultrastrong coupling conditions, the pulsed modulation of the cavity frequency can adiabatically produce mid-infrared light that is simultaneously sub-Poissonian and quadrature squeezed, depending on the dipolar behavior of the vibrational mode. For a vibration-cavity system in strong coupling, non-adiabatic polariton excitations can be produced after the frequency modulation pulse is over, when the system is initially prepared in the lower polariton state. We propose design principles for the generation of mid-infrared quantum light by analyzing the dependence of the cavity field statistics on the shape of the electric dipole function of the molecule, the cavity detuning at the modulation peak and the anharmonicity of the Morse potential. Feasible experimental implementations of the modulation scheme are suggested. This work paves the way for the development of molecule-based mid-infrared quantum optical devices at room temperature. © 2022 The Author(s). Published by IOP Publishing Ltd on behalf of the Institute of Physics and Deutsche Physikalische Gesellschaft.
Keywords: molecular polaritons; quantum light; mid-infrared resonators; molecular vibrations; cavity QED; quantum squeezing; ultrastrong coupling